The Effects of an Exercise Program on Pain and Range of Motion in Frozen Shoulder Patients - นกหนู, สายใจ; บกสวัสดิ์, มณีภรย์; อาม๊ะ, มุคลิส (Princess of Naradhiwas University Journal, 2018)
This quasi-experimental research aimed to compare the average pain scores and average degree of shoulder motion in patients with frozen shoulder between control group performed standardized physical therapy and experimental group performed standardized physical therapy and exercise program. The samples were 60 frozen shoulder patients divided into 2 groups with 30 subjects in each group by simple random sampling. The instruments used in research included: general information questionnaire, physical examination and treatment record, standardized physical therapy program and exercise program. Data were analyze by descriptive statistics and t-test. The findings demonstrated that the exercise programs with standardized physical therapy decreased the pain score significantly, increased degree of shoulder flexion, extension, abduction, adduction and internal rotation significantly compare to the standard physical therapy (p < 0.05). But the degree of shoulder external rotation between two groups are not significant differences (p> 0.05). Conclude that the exercise program reduces the pain level and increases the degree of shoulder motion. It can be used for physical therapy and should be developed for more effective treatment.